2010
DOI: 10.1007/s10639-010-9146-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a novel application of web-based technology to support implementation of school wellness policies and prevent obesity

Abstract: Childhood obesity is one of the most pressing public health concerns in the United States. Because schools are a critical site to promote wellness and prevent obesity, extensive policy and legislative efforts have focused on school-based food services, nutrition education, physical education, and overall physical activity. Unfortunately, research indicates that most of these policies prove ineffective due to insufficient implementation. A small number of web-based programs have emerged that are designed to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…A second implication involves eTools as a de facto surveillance system. Intended to help school nurses be more efficient and designed to produce routine utilization reports, when employed on a large scale eTools compiles accurate mineable data that can generate actionable results using few additional resources . The current study demonstrated the efficacy of this eTools function, which could conceivably be expanded to investigate many other health issues including diabetes, asthma, allergies, immunizations, screening results, and injuries.…”
Section: Implications For School Healthmentioning
confidence: 84%
See 1 more Smart Citation
“…A second implication involves eTools as a de facto surveillance system. Intended to help school nurses be more efficient and designed to produce routine utilization reports, when employed on a large scale eTools compiles accurate mineable data that can generate actionable results using few additional resources . The current study demonstrated the efficacy of this eTools function, which could conceivably be expanded to investigate many other health issues including diabetes, asthma, allergies, immunizations, screening results, and injuries.…”
Section: Implications For School Healthmentioning
confidence: 84%
“…Previous evaluation found eTools to be a comprehensive, well‐designed program with the potential to support school wellness policies. Web‐based features provide school nurses with tools and resources for working more efficiently . Owing to eTools' proven benefits and ongoing support from InnerLink, school nurses across Pennsylvania routinely collect and report expansive amounts of potentially valuable student health information that can be subjected to data‐mining techniques…”
mentioning
confidence: 99%
“…10 Along with unique identifiers, gender, and date of birth, medical data were compiled in a data repository maintained by InnerLInk (Lancaster, PA), the company that provides Health eTools at no cost to schools through funding from the Highmark Foundation. 9 All applicable federal and state safeguards of family and student rights, both medical and educational, were followed in the compilation of these data. Access was provided to deidentified data on the InnerLink server via a password-protected Internet link.…”
Section: Methodsmentioning
confidence: 99%
“…The attention given to youth problems such as substance use and violence on or off campus is growing (1) and numerous studies have been done to understand such adolescent development issues (2,3). In response to the growing adolescent problems, many prevention and intervention programs have been designed and implemented, with some of them proven to be effective (1,4). Shek (2) investigated and reviewed adolescent developmental problems in Hong Kong, including substance abuse, adolescent crime especially shoplifting and stealing, adolescent mental health problems such as psychosis and anxiety, unhealthy life styles such as smoking and early sexual behaviors, family problems, and the growing number of those living in poverty or unemployed.…”
Section: Introductionmentioning
confidence: 99%